Analysis of Factors That Affect Community Participation on City without Slums Program (KOTAKU) in Percut Sei Tuan District Deli Serdang Regency - Nenny Rosalinda Siburian; Erika Revida; Suwardi Lubis (Budapest International Research and Critics University, 2021)
The City without Slums (KOTAKU) program is one of the government's strategic efforts to accelerate the handling of slums in Indonesia and support the